Respuesta :
To find the value of your expression, you could use the following steps;
First lets substitute the value of x in the equation;
7 + 2(-3 - 9) - (-3+ 2)
Next, simplify the parenthesis;
7 + 2(-12) - (-1)
7 - 24 + 1 = -16
So your final answer would be; -16
First lets substitute the value of x in the equation;
7 + 2(-3 - 9) - (-3+ 2)
Next, simplify the parenthesis;
7 + 2(-12) - (-1)
7 - 24 + 1 = -16
So your final answer would be; -16
sub -3 for every x
7+2(-3-9)-(-3+2)
PEMDAS
simplify inside parenthases first
-3-9=-12
-3+2=-1
now we have
7+2(-12)-(-1)
multiplictaion
2(-12)=-24
-(-1)=1
now we have
7-24+1
-17+1
-16 is reault
7+2(-3-9)-(-3+2)
PEMDAS
simplify inside parenthases first
-3-9=-12
-3+2=-1
now we have
7+2(-12)-(-1)
multiplictaion
2(-12)=-24
-(-1)=1
now we have
7-24+1
-17+1
-16 is reault